PROFITABILITY RATIO ANALYSIS AS A MEASURE OF FINANCIAL PERFORMANCE OF PT MALINDO FEEDMILL TBK FOR THE 2021-2024 PERIOD - Dani, Rahmat; Usmar, Andi (PT. Jurnal Center Indonesia Publisher, 2026)
This study was conducted to analyse profitability ratios as a measure of financial performance at PT Malindo Feedmill Tbk (MAIN) for the period 2021-2024. The animal feed industry faces challenges of high production costs, ranging from 85-90%, as well as dependence on unstable imported raw materials. The research method used is quantitative descriptive with purposive sampling techniques on the company's consolidated financial statements. The indicators used to analyse the data include Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). In 2022, net profit fell sharply by 57% to RP 27 billion due to production cost pressures. However, in 2024, the company managed to recover with a net profit of RP 489.8 billion. This unique finding shows an increase in Return on Assets (ROA) of 9.10% in 2024 despite a decline in assets. This shows that management has succeeded in eliminating unproductive assets and optimising production efficiency. The effectiveness of cost transformation and the company's operational resilience to market fluctuations are reflected in a Return on Equity (ROE) of 18.61% at the end of the period.